Correlation of dermal and blood eosinophilia with bullous pemphigoid disease severity - Farshad Farnaghi, MD; Amir-hooshang Ehsani, MD; Kambiz Kamyab-Hesary, MD; Sepideh Abbasian, MD; Hasan Seirafi, MD; Maryam Nasimi, MD (Wolters Kluwer, 2020)
Background: Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disease associated with immune response against BP-180 and BP-230. Peripheral blood eosinophilia and dermal infiltration of eosinophils are common findings in BP. Objective: The aim of our study was to demonstrate a statistical correlation between dermal and peripheral blood eosinophilia, anti BP-180, and anti BP-230 IgG and clinical severity of BP. Methods: A total of 27 patients with newly diagnosed BP were included. Severity of disease was assessed according to the bullous pemphigoid disease activity index (BPDAI). Anti-BP-180 and anti-BP-230 titers, peripheral blood eosinophilia, and dermal eosinophil infiltration and tissue inflammation severity were assessed for each patient. Results: A significant correlation was found between the serum levels of anti-BP-180 and anti-BP-230, and dermal eosinophilia and tissue inflammation severity with objective and subjective BPDAI scores. In addition, there was a significant correlation between the percentage of peripheral blood eosinophils and subjective BPDAI scores and urticarial/eczematous lesions. Moreover, the mucosal component did not show any correlation with autoantibody levels and inflammation severities. Conclusion: Anti-BP-180 and anti-BP-230 levels, tissue inflammation severity, and dermal eosinophilia had a strong and significant correlation with BP severity. In addition, percentage of peripheral blood eosinophilia showed a correlation with subjective BPDAI scores.